For-Profit Social Ventures - Dees, L. Gregrory; Battle Anderson, Beth (Senate Hall, 2004)
Traditional sector boundaries are breaking down as societies search for more innovative, cost-effective, and sustainable ways to solve social problems and provide socially important goods, such as education and health care. One result has been a rise in the number of social entrepreneurs who want to combine a social purpose with a for-profit organizational structure. Is the wealth-creation imperative inherent in for-profit organizations really compatible with optimal social impact? This paper is designed to help would-be for-profit social entrepreneurs understand and address the challenges of using a for-profit organization to serve a social objective. Drawing on a wide range of literature as well as case studies, we identify the challenges facing for-profit social ventures and outline strategies for responding. Of course, there are limits to what can be done within a for-profit structure. Our analysis should help social entrepreneurs recognize those limits and respond to them intelligently as they design their organizations.
Keywords: social entrepreneurship|social enterprise|social purpose business|social impact|social ventures|social sector|entrepreneurship